PENGUKURAN LEBAR LAUT TERITORIAL MENGGUNAKAN GARIS PANGKAL MENURUT UNCLOS 1982 DAN PENERAPANNYA DALAM HUKUM INDONESIA - Eva Johan (Faculty of Law, Universitas Jenderal Soedirman, 2009)
Arrangement of concerning wide determination the territorial of sea is conducted by withdrawal the jetty lines that done by harmonizing the regulation of the stipulating the useful of the archipelago jetty lines that matching with region of NKRI by positive law instrument of Indonesia. But which require to be reemphasized is Indonesia obligation to make a map of the regional border line of Indonesia, because till in the end Indonesia still use the illustrative map that made in the 1960 year. The government of Indonesia have to immediately make the map of the region of Indonesia by using dot co-ordinate of the jetty lines of Indonesia archipelago which have been specified according to PP No.37 year 2008 to take care the sovereignty of Indonesia. Kata kunci : pengukuran lebar laut territorial, garis pangkal dan hukum Indonesia.